Utilization of Social Technique For Quality Control In Building Construction : A Review - Deepak Premchand Shah; Dipali Jaiswal (International Journal of Scientific Research in Civil Engineering, 2021)
With the progress of the times, the construction industry has undergone great changes and development, and has received more attention. When people treat a thing, it is necessary to consider its quality. The quality of engineering is of vital importance to a construction project, which should not only meet people’s living needs, but also guarantee people's life and property safety. Therefore, this article will from the significance of quality management and control in the construction engineering, respectively discuss the architectural engineering quality problems causes and solutions, so as to effectively enhance the level of the current construction project quality. In fact, it is also a ‘shortcut’ to improve the competitiveness of enterprises.Construction industry plays an important role in the development of any country. The development of the construction industry depends on the quality of construction projects. Quality is one of the critical factors in the success of construction projects. Improvement in the quality of construction projects is linked with quality management in the project life cycle. Although quality management at every stage of the project life cycle is important , quality management at the execution (construction) stage contributes significantly to the final quality outcome of construction projects. This project mainly focuses on the importance and factors that affect the quality management in the execution (construction) phase. The project also includes visiting some construction companies and conducting the questionnaire survey, then analyse the difficulties (major factors) and the cost variance due to quality defect in quality management and suggest some proactive measures for the improvement of quality in the execution phase of construction projects.
Keywords: Quality Control; Complex; Topography; Geology; Hydrology; Construction Technology